2013
DOI: 10.7567/jjap.53.014001
|View full text |Cite
|
Sign up to set email alerts
|

Novel gate-all-around polycrystalline silicon nanowire memory device with HfAlO charge-trapping layer

Abstract: Gate-all-around (GAA) nanowire (NW) memory devices with a SiN-or Hf-based charge-trapping (CT) layer of the same thickness were studied in this work. The GAA NW devices were fabricated with planar thin-film transistors (TFTs) on the same substrate using a novel scheme without resorting to the use of advanced lithographic tools. Owing to their higher dielectric constant, the GAA NW devices with a HfO 2 or HfAlO CT layer show greatly enhanced programming/erasing (P/E) efficiency as compared with those with a SiN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Based on these two features the programming current for fast program operation can be approximated in the range of 10 −2 A=cm 2 , which is consistent with program constraint defined in Table I. 14) Figure 6 shows the P=E characteristics of simulation and experimental data in Ref. 8 being benchmarked to GAA-FG of 6 nm SiO 2 tunnel layer. Generally, it can be observed that the triangular channel of GAA-FG has comparable memory window to 6 nm SiO 2 .…”
Section: Simulation Validation Of Gaa-fgsupporting
confidence: 54%
See 3 more Smart Citations
“…Based on these two features the programming current for fast program operation can be approximated in the range of 10 −2 A=cm 2 , which is consistent with program constraint defined in Table I. 14) Figure 6 shows the P=E characteristics of simulation and experimental data in Ref. 8 being benchmarked to GAA-FG of 6 nm SiO 2 tunnel layer. Generally, it can be observed that the triangular channel of GAA-FG has comparable memory window to 6 nm SiO 2 .…”
Section: Simulation Validation Of Gaa-fgsupporting
confidence: 54%
“…8,9) However, it did not describe the subthreshold degradation of the device. In the absence of short channel effects, interface trap charge is the one who responsible for the subthreshold degradation in GAA structure.…”
Section: Simulation Validation Of Gaa-fgmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the trade-off between data retention and program/erase speed is the main bottleneck for SONOS devices in replacing floating-gate ones. 12 Recently, high-κ dielectrics have been [13][14][15][16][17][18] Therefore, in this work, to further improve NOR-type flash memory performance, we propose and investigate a type of p-channel charge trapping FOI-MAHAS memory. In the Fabrication process section, we briefly introduce the specific process flow of the p-channel charge trapping FOI-MAHAS memory.…”
mentioning
confidence: 99%